2019
DOI: 10.1002/aqc.3073
|View full text |Cite
|
Sign up to set email alerts
|

Fishers' experiences and perceptions of marine mammals in the South China Sea: Insights for improving community‐based conservation

Abstract: 1. The successful conservation of marine mammals is often dependent upon support from local fishing communities, and valuable conservation insights can be obtained through understanding fishers' attitudes and awareness of marine mammals. A new local ecological knowledge dataset was obtained through large-scalequestionnaire-based interviews with 510 artisanal fishers from 16 coastal fishing communities around Hainan, China. Almost all respondents (92.7%) reported regular encounters with marine mammals. Many res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Once a significant effect was found for either main factor, we performed the Kruskal-Wallis tests to make post hoc pairwise multiple comparisons using Tukey's HSD (equal variances, p > 0.05) or Tamhane's T2 method (unequal variances, p < 0.05). We also built and pruned a classification and regression tree (CART), in order to determine which variable is predominant in affecting the IPHD group sizes (De'ath and Fabricius, 2000;Liu et al, 2019). Results on IPHD group sizes are reported as mean ± standard deviation (SD) unless otherwise stated.…”
Section: Discussionmentioning
confidence: 99%
“…Once a significant effect was found for either main factor, we performed the Kruskal-Wallis tests to make post hoc pairwise multiple comparisons using Tukey's HSD (equal variances, p > 0.05) or Tamhane's T2 method (unequal variances, p < 0.05). We also built and pruned a classification and regression tree (CART), in order to determine which variable is predominant in affecting the IPHD group sizes (De'ath and Fabricius, 2000;Liu et al, 2019). Results on IPHD group sizes are reported as mean ± standard deviation (SD) unless otherwise stated.…”
Section: Discussionmentioning
confidence: 99%
“…Local ecological knowledge data were collected following a standardized methodological protocol developed for conservation research in Chinese fishing communities [ 16 ] and previously applied to research on SCS marine mammals [ 17 , 18 ]. Interviews were conducted using a questionnaire that took approximately 45 min to complete and included a combination of multiple choice, short free response and multi-part questions (electronic supplementary material).…”
Section: Methodsmentioning
confidence: 99%
“…Sanguinetti et al (2021) found that older fishers with less formal education have a high focus on maximizing fishing yield, while younger fishers have a more sustainable and conservationist view of fishing. Similarly, Liu et al (2019), found that artisanal fishers' perceptions of marine mammals were predicted by fishing experience and education level. Therefore, it is relevant to include these parameters in studies of this type.…”
Section: Data From the Observers Vs Fishersmentioning
confidence: 99%